Improving availability by lean manufacturing and TPM tools in an SME in the plastics sector - Acuña Damiano, Valeria Belen (2024)
This study focused on improving the productivity of a Medium and Small Enterprise (MYPE) in the plastic sector through the application of Lean Manufacturing. The MYPE had low productivity due to delays in changing molds in its production processes. The study aimed to increase the availability of machinery and reduce mold changeover time to improve productivity. The approach was a continuous improvement strategy, which involved identifying and eliminating waste, simplifying processes, improving material handling efficiency, and implementing a preventive maintenance system. A root cause analysis was conducted to determine the leading causes of delays in mold changeover, and solutions were implemented to reduce changeover time. The results showed a significant reduction in mold changeover time, which increased machinery availability and improved productivity. Furthermore, waste was eliminated, and efficiency in material management was improved, leading to reduced operating costs. In conclusion, Lean Manufacturing proved to be an effective strategy to enhance productivity in a MYPE facing mold changeover delays. This approach can benefit other companies facing similar issues in their production processes.